1989
DOI: 10.1515/znc-1989-3-403
|View full text |Cite
|
Sign up to set email alerts
|

New Dihydrobiflavones from the Moss Plagiomnium cuspidatum

Abstract: In Plagiomnium cuspidatum the three new dihydrobiflavones 2,3-dihydro-5′-hydroxyam entoflavone, 2,3-dihydro-5′,3‴-dihydroxyamentoflavone and 2,3-dihydro-5′-hydroxyrobustaflavone were detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…ZINC000043552589, ZINC000003594862, ZINC000003947429 and ZINC000070691536 with docking energy −10.5, −9.8, −9.5 and −9.4 kcal/mol, respectively, with favorable binding affinity in the active pocket of SARS-CoV-2 M pro were considered for further analysis. Here, ZINC000043552589 was identified as 2,3-Dihydroamentoflavone, an amentoflavone-type bioflavonoid was first isolated from Cycas revoluta [ 53 ]. Likewise, ZINC000003594862 (Podocarpusflavon-B) was reported as an amentoflavone and extracted from Selaginella sinensis (Selaginellaceae) herb [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…ZINC000043552589, ZINC000003594862, ZINC000003947429 and ZINC000070691536 with docking energy −10.5, −9.8, −9.5 and −9.4 kcal/mol, respectively, with favorable binding affinity in the active pocket of SARS-CoV-2 M pro were considered for further analysis. Here, ZINC000043552589 was identified as 2,3-Dihydroamentoflavone, an amentoflavone-type bioflavonoid was first isolated from Cycas revoluta [ 53 ]. Likewise, ZINC000003594862 (Podocarpusflavon-B) was reported as an amentoflavone and extracted from Selaginella sinensis (Selaginellaceae) herb [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…15,16 dihydroxyamentoflavone. 17 Analysis of both the ECD spectrum ( Figure S20, Supporting Information) and optical rotation indicated that biflavonoid 2 was present as a racemic mixture.…”
Section: Resultsmentioning
confidence: 99%
“…The proposed molecular formula of C 30 H 20 O 12 for compound 2 was confirmed by the assignment of the [M + H] + to the peak observed in the HRESIMS spectrum at m / z 573.1044. The structure of compound 2 was defined through extensive NMR analyses as the known biflavonoid 8-[5-(5,7-dihydroxy-4-oxochroman-2-yl)-2,3-dihydroxyphenyl)-2-(3,4-dihydroxyphenyl]-5,7-dihydroxy-4 H -chromen-4-one, or 2,3-dihydro-5′,3‴-dihydroxyamentoflavone . Analysis of both the ECD spectrum (Figure S20, Supporting Information) and optical rotation indicated that biflavonoid 2 was present as a racemic mixture.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The detailed extraction o f P. cuspidatum is de scribed in [11]. T he m ethanolic ex tract o f P. elatum was separated by repeated colum n and pap er ch ro m ato g rap h y w ith the solvent systems as listed in T able I. F inal purification o f the isolated com p o unds was achieved on Sephadex LH 20 w ith aqueous M eO H as eluent.…”
Section: E Xtraction and Isolationmentioning
confidence: 99%